Analisis Pengaruh Faktor Perusahaan dan Auditor Terhadap Audit Delay (Studi Empiris Pada Sektor Konsumen Primer Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2020) - Sindy Jhony Ver; Anda Dwiharyadi; Afridian Wirahadi Ahmad (Politeknik Negeri Padang, 2023)
This study aims to analyze empirical evidence of the effect of firm size, profitability, solvency, operating profit and loss, KAP size, audit opinion, and audit committee on audit delay. Company factor is proxied by company size, profitability, solvency, operating profit and loss, and audit committee. Meanwhile, the auditor factor is proxied by the size of the public accounting firm, and the auditor's opinion. The population in this study are companies engaged in the Non-Cycle Consumer sector which are listed on the Indonesia Stock Exchange for the 2018-2020 period. The sampling technique in this study used purposive sampling. So that the sample obtained from purposive sampling is 43 companies. The analytical method used is multiple linear regression, using SPSS software. The results of this study indicate that the company's factors consisting of operating profit and company profitability have an effect on audit delay. Meanwhile, the firm's factors on firm size, solvency, and audit committee have no effect on audit delay. And the auditor factor shows that the size of the KAP and audit opinion have an effect on audit delay.